The Role of Employees And Their Competencies In The Fourth Industrial Revolution - Beata HYSA (Communications of International Proceedings, 2021)
To implement Industry 4.0, organizations need to transform and adapt their resources to the new needs. The transformation demands a significant investment in the latest technology and the competencies of engineers who will manage it. The implementation of Industry 4. means, in most cases, automation of many processes, but it does not eliminate the human factor. For some activities, it will be the people who support and supplement the machines. The main goal of the research is to show the essential role of the employee and the competencies to implement Industry 4.0 effectively. As a result of the analysis, it was found that the human factors are appreciated in Polish manufacturing companies implementing Industry 4.0, but some efforts are needed. The research shows that employees are resistant to ICT and social skills training. While eager to share their knowledge, they are reluctant to learn new things. The respondents also indicated personal, conceptual, and interpersonal competencies as crucial competencies. The theoretical discussion in the presented paper was supported by research conducted simultaneously and on a similar group of respondents in Poland among Polish enterprises.
Keywords: Competencies; Industry 4.0; Employees